Males and Females in Social Solidarity Economy: Voices from Latin America - Heras Monner Sans, Ana Ines (2014)
Gender relationships have been a contested terrain over time in Latin America. As it has been documented elsewhere (Heras 2012), societies in Latin America are oriented by patriarchy. The participation of males in household domestic chores or in what has been seen as traditionally feminine tasks still waits to be a reality.  Conversely, males are still predominant in decision-making roles regarding political participation and economic resources, and they tend to do better in access to economic resources. It is true that much has been gained for women over the decades, in particular if we compare current public policy measures or legislative frameworks with those of the past two centuries in regards to securing women's rights. Yet, gender inequality is still at place. Differences can be seen in what women earn (for the same qualified job), in whether or not females can access political participation, how domestic chores and responsibilities are distributed, and how women and men are perceived as not equally capable for specific tasks.